Characterising bremsstrahlung and non-linear Compton scatter in high intensity laser-foil interactions - Morris, Stuart (Cranfield University, 2020)
Non-linear Compton scatter (NCS) and bremsstrahlung radiation both contribute to the X-rays produced in laser-solid interactions. While it is expected that NCS will efficiently generate X-rays for next generation lasers, the weaker NCS yields from laser-solid interactions in existing facilities have not yet been observed due to the bremsstrahlung background. This work attempts to derive a quantitative description of the bremsstrahlung efficiency, for interactions between ultrahigh-intensity short-pulse lasers and thin-foil targets. This model was tested against simulations from the particle-in-cell code EPOCH, which has been extended to include bremsstrahlung modelling capabilities. The relative efficiencies of bremsstrahlung and NCS will be compared to seek NCS signatures for experimental observation.
Keywords: 'Bremsstrahlung'; 'Laser'; 'Synchrotron'; 'DSDS19 Poster'; 'DSDS19'; 'Condensed Matter Imaging'; 'Lasers and Quantum Electronics'